Rape Myth Acceptance in the Digital Age: The Effects of Using Dating Apps and the Moderation Role of Gender - Luye Li (Human Behavior and Emerging Technologies)
Rape myth acceptance (RMA) is a crucial predictor of rape proclivity. It has been extensively analyzed for its gender differences to aid in designing clinical interventions and health programs. Although it is well known that males generally exhibit higher levels of RMA than females, the impact of digital devices, the Internet, and dating apps on RMA and how this impact differs between genders remain understudied. This study addresses these gaps by examining a sample of 647 Chinese-speaking college students in Canada. The findings indicate that the use of dating apps is positively associated with higher RMA; male students exhibited greater RMA levels than female students; and gender moderates the impact of dating app usage, with a more elevated effect on RMA observed in male students compared to female students. The study’s limitations are discussed, including the specificity of the sample (Chinese college students in Canada) and caution against generalizing to broader populations, along with the research and policy implications of the study.